2000
DOI: 10.1002/1096-9861(20000101)429:1<71::aid-cne6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the spatial relationship between nicotinamide adenine dinucleotide phosphate-diaphorase activity, serotonin immunoreactivity, and GYIRFamide immunoreactivity and the musculature of the adult liver fluke,Fasciola hepatica (Digenea, Fasciolidae)

Abstract: This is the first detailed description of the nitrergic nervous system in a fluke. In this study, the authors analysed the distribution of the nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) reactivity in neuronal and nonneuronal tissues of the adult fluke Fasciola hepatica and compared this with the distribution of the musculature using tetramethylrhodamine isothiocyanate-phalloidin. To assess the correlation between the number of muscle cells in different parts of the fluke and the NADPH-d-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
5
0
8
Order By: Relevance
“…Paralysis and putative vermifugal activity in trematodes have been attributed to an increase in nitric oxide (NO) production [52]. It has been suggested that NO acts as neurotransmitter at the neuromuscular junction [53] and causes myoinhibition [54] in helminth parasites. Kar et al (2002) observed increases in neuronal nitric oxide synthase (nNOS) activity and NO release in worms treated in vitro with 1.85 mM pure genistein.…”
Section: Effects Of Flavonoids On Helminthsmentioning
confidence: 99%
“…Paralysis and putative vermifugal activity in trematodes have been attributed to an increase in nitric oxide (NO) production [52]. It has been suggested that NO acts as neurotransmitter at the neuromuscular junction [53] and causes myoinhibition [54] in helminth parasites. Kar et al (2002) observed increases in neuronal nitric oxide synthase (nNOS) activity and NO release in worms treated in vitro with 1.85 mM pure genistein.…”
Section: Effects Of Flavonoids On Helminthsmentioning
confidence: 99%
“…The first observations of the NADPH-diaphorase (NADPH-d) reaction, indicating the presence of nitrergic nerve cells and fibres in the NS of flatworms, were made in adult Hymenolepis diminuta by Gustafsson et al (1996) and in the free-living flatworm Dugesia tigrina by Eriksson (1996). Since then, nitrergic nerve cells and fibres have been detected with the same method in adult Diphyllobothrium dendriticum , adult Planaria torva , tetrathyridia of Mesocestoides vogae (Terenina et al 1999), adult Fasciola hepatica (Gustafsson et al 2001), adult Fasciolopsis buski (Tandon et al 2001), and in cercaria of Diplostomum chomatophorum (Terenina and Gustafsson 2002). A radiometric analysis of the activity of nNOS in H. diminuta was performed by Terenina et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…This debate is mainly due to the fact that sufficient ultrastructural information has so far been lacking about the nervous system of the platyhelminths, especially of OV (Leksomboon et al, 2012a), in spite that there have been ample numbers of immuno-fluorescence microscopic studies of the peripheral and central nervous systems in the platyhelminths in which numerous neuron somata are clearly demonstrated in the immuno-light microscopy (Barton et al, 1993;Gustafsson et al, 2001Gustafsson et al, , 2002Leksomboon et al, 2012b). The lack thereof, seems to be understandable because it is technically impossible to examine at the electron microscopic level the immuno-labeled neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such knowledge may provide alternative drug targets for anthelminthics. The nervous system of the platyhelminths including the OV has been studied in immunofluorescence histochemistry at light microscopic levels with antibodies against several neurotransmitters and neuromodulators, whose functions are known to work largely in the motor nervous system (Gustafsson et al, 2001(Gustafsson et al, , 2002. However, there has so far, been neither ultrastructural knowledge of moter neurons of these parasites nor light and electron microscopic information of their peripheral sensory neurons (Leksomboon et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%